Microwave irradiation consequences on chemical reagent consumption in ilmenite flotation. Issue 2 (3rd April 2017) - Salmani Nuri, Omid; Irannajad, Mehdi; Mehdilo, Akbar
ABSTRACT: The effect of microwave irradiation on chemical reagent consumptions in the ilmenite flotation process was investigated. The flotation tests have been carried out in two stages of micro and mechanical agitation cells. The microwave irradiation increased the contact angle about 25% within 4 minutes of flotation. The adsorption results after irradiation indicated that in the presence of the activator (lead II nitrate), the collector (sodium oleate) adsorption on the ilmenite surface is increased, whereas in the presence of depressant (acidified sodium silicate), the collector adsorption on the olivine-pyroxene surface is decreased. The microflotation results showed that despite the decreasing in the collector dosage up to 50%, the recovery increased about 3.17% after irradiation. In this condition, the consumption of depressant and activator decreased 50%. The results of mechanical agitation flotation after irradiation showed that not only the dosages of collector, activator and depressant are decreased 25%, 50% and 50%, respectively, but also the recovery and separation efficiency of ilmenite flotation are increased 6.29% and 2.63%, respectively. These results confirmed the microflotation results. Microwave pretreatment improved the time of ilmenite hydrophobicity, collector adsorption is confirmed by contact angle and adsorption analysis and had a good corresponding to the flotation recovery.